Eletrodos de pasta de carbono modificados com Mn-porfirina ou Mn-porfirina imobilizada em argilominerais: caracterização eletroquímica e eletrocatálise de redução do peróxido de hidrogênio - Lima, Caio Vinícius de (2017)
In this work, hybrid materials were prepared by immobilizing cationic Mn-porphyrins (MnP) on palygorskite clay mineral and carbon paste electrodes (CPE) were modified with Mnporphyrin or palygorskite-based (Palygo/MnP) or vermiculite-based (Verm/MnP) hybrid materials. In addition to the characterization of the hybrid materials and modified electrodes, one of the modified electrodes was studied for H2O2 electroreduction in aqueous milieu. The immobilization of the three isomers of Mn(III) N-methylpyridylporphyrin, Mn(III)TM-XPyPCl5 (X = 2, 3 and 4), on sodium palygorskite followed a protocol previously established for the vermiculite-based (Verm/MnP) counterparts, yielding Paligo/Mn(III)TM-X-PyPCl5 (X = 2, 3 and 4) materials in quantitative yields. MnP incorporation on palygorskite was characterized by diffuse reflectance spectroscopy. X-ray diffractometry analyses showed that MnP immobilization did not affect significantly the palygorskite structure. The electrochemical studies were carried out with the most common MnP isomer, Mn(III)TM-4-PyPCl5, and included the construction of the following modified electrodes: CPE+Mn(III)TM-4-PyPCl5, CPE+Palygo, CPE+Palygo, CPE+Palygo/Mn(III)TM-4-PyPCl5 and CPE+Verm/Mn(III)TM-4PyPCl5. All the modified CPE were characterized by cyclic voltammetry and electrochemical impedance spectroscopy techniques. Whereas CPE+Verm disintegrated upon contact with the electrolytic solution, all other modified CPE showed both electrochemical activity and mechanical stability. All CPE modifications increased the carbon-paste matrix conductivity, led to more reversible [Fe(CN)6]3-/[Fe(CN)6]4- oxidation/reduction processes, and facilitated electron transfer on the electrode surface. Finally, the electrocatalytic behavior of EPC+Mn(III)TM-4-PyPCl5 was evaluated against the electrocatalytic reduction of H2O2 in aqueous milieu. Despite the low percentage of MnP incorporated onto CPE+Mn(III)TM-4PyPCl5 (0.012% w/w), the MnP-modified electrode behaved as a good amperometric sensor for H2O2 detection and quantification. The analytical curve showed two linear regions: i) from 20 µmol L-1 to 120 µmol L-1, and ii) from 0.20 mmol L-1 to 2.10 mmol L-1. For the higher concentration region, the limits of detection and quantification were 5.8 µmol L-1 and 19.2 µmol L-1, respectively, with relatively high sensibility of 6.9 µA L mmol-1.